Analisis Unsur Intrinsik Cerpen “Ketika Laut Marah” Karya Widya Suwarna Menggunakan Pendekatan Objektif - Wanda Siti Nur Azizah; Intan Silfiani (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
This researchg aims to analyzing the short story "When the Sea is Angry" by Widya Suwarna using an objective approach to obtain the structure in a short story in the form of intrinsic elements, namely theme, point of view, plot, setting, characters, characterization, language style and message in the short story. The research method used is descriptive qualitative, this research method is devoted to researching thoroughly, broadly and in depth. The results are in the quality of words, sentences and their meaning without comparing the results of this research with the results of other studies. The source of data obtained was by reading the short story "When the Sea is Angry" by Widya Suwarna carefully and critically. Based on the results of the theme contained in the short story, namely about sincerity, that even if we have the smallest fortune, when we see our neighbors or relatives who are experiencing difficulties, we must help and share sincerely and sincerely.This is in line with the character in the short story "When the Sea is Angry" by Widya Suwarna, namely Pak Yus, who has a caring and sincere attitude in helping his neighbors.